Non-specific neck pain in schoolchildren: prognosis and risk factors for occurrence and persistence. A 4-year follow-up study - Ståhl, Minna; Kautiainen, Hannu; El-Metwally, Ashraf; Häkkinen, Arja; Ylinen, Jari; Salminen, Jouko J; Mikkelsson, Marja (Pain (Amsterdam), 2008)
This study investigated the natural course of neck pain (NP) in 9-12-year-olds during a 4-year follow-up. Risk factors for the occurrence and persistence of weekly NP were explored separately for boys and girls. At baseline, 1756 schoolchildren completed a questionnaire eliciting musculoskeletal pain symptoms, other physical, and psychological symptoms and frequency of physical activity, and were tested for joint hypermobility. Symptoms during the preceding three months were asked using a five-level frequency classification. Re-evaluation was performed after one and four years using identical questionnaires. During follow-up, 24% reported none, 71% fluctuating, and 5% persistent weekly NP. The frequency of NP at baseline was linearly related to weekly NP during follow-up in both genders (P<0.001). Furthermore, a significant increasing linear trend towards a more persistent course of NP was seen in children with weekly other musculoskeletal and/or other physical and psychological symptoms at baseline. Among originally neck pain-free pre-/early adolescents, weekly other musculoskeletal pain symptoms (only in girls) and other physical and psychological symptoms (in both genders) predicted the occurrence of weekly NP during follow-up. In conclusion, neck pain in schoolchildren tends to fluctuate, but there also seems to exist a subgroup (5%) with persistent NP already in pre-/early adolescents, or even earlier. Co-occurrence of frequent other musculoskeletal symptoms and/or markers of psychological stress with frequent NP are risk indicators for a more persistent course, at least within next few years. Since adult chronic NP problems might originate in childhood, further studies are needed, including preventive interventions.